Characterization and diagnostic evaluation of chronic polyneuropathies induced by oxaliplatin and docetaxel comparing skin biopsy to quantitative sensory testing and nerve conduction studies. (25th January 2014) - Krøigård, T.; Schrøder, H. D.; Qvortrup, C.; Eckhoff, L.; Pfeiffer, P.; Gaist, D.; Sindrup, S. H.
<x xml:space="preserve">Abstract</x> Background and purpose Chemotherapy‐induced peripheral neuropathy negatively affects the quality of life for many patients treated with oxaliplatin or docetaxel for gastrointestinal cancer or breast cancer. Symptoms can persist long after treatment and often include neuropathic pain. Our objective was to characterize the neuropathies with regard to symptoms, neurological signs and objective evidence of damage to the structure and function of the peripheral nerves. Furthermore, the diagnostic values of skin biopsy, quantitative sensory testing (QST) and nerve conduction studies (NCS) were compared. Methods Patients complaining of neuropathy symptoms at least 3 months after completion of treatment with oxaliplatin (n = 20) or docetaxel (n = 20) were recruited from the Department of Oncology or using hospital records. Neuropathy scores were determined along with the intraepidermal nerve fibre density in skin biopsies from the proximal and distal parts of the leg, QST and NCS. Results Clinically only sensory functions were affected. In general, neuropathy scores were higher in the oxaliplatin‐treated group. Both sensory and motor fibres were affected in the NCS, showing predominantly signs of axonal damage. Mechanical detection threshold was most often affected in the QST. NCS, QTS and skin biopsy were abnormal in 11, 13 and 17 and 7, 11 and 15 of the oxaliplatin‐treated patients and docetaxel‐treated patients, respectively. Conclusions Chemotherapy‐induced peripheral neuropathy after oxaliplatin or docetaxel treatment is a clinically sensory, axonal neuropathy affecting only small nerve fibres in some patients. NCS are often normal, whereas QST and skin biopsy have a higher diagnostic sensitivity.